2009
DOI: 10.1080/03079450802632031
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and growth characteristics of selected infectious laryngotracheitis virus strains from the United States

Abstract: In a recent study, several US infectious laryngotracheitis virus (ILTV) strains and field isolates were genotyped by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) into nine different genotypes. All of the commercial poultry isolates were identified within genotypes IV, V, and VI. Based on the PCR-RFLP, Group IV isolates were characterized as genetically identical to the chicken embryo origin (CEO) vaccines, Group V as genetically closely related to the CEO vaccines, and Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 22 publications
(20 reference statements)
3
47
0
2
Order By: Relevance
“…This is consistent with previously reported results, indicating that greater viral replication was detected in the respiratory organs (Oldoni et al, 2009;Rodríguez Avila et al, 2007). However, other organs, such as the lungs, cecal tonsils, digestive tract, and kidneys were also positive.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is consistent with previously reported results, indicating that greater viral replication was detected in the respiratory organs (Oldoni et al, 2009;Rodríguez Avila et al, 2007). However, other organs, such as the lungs, cecal tonsils, digestive tract, and kidneys were also positive.…”
Section: Discussionsupporting
confidence: 83%
“…Recent experimental studies indicate that the virus can also be detected in other organs, such as the heart, liver, spleen, lung, kidney, tongue, thymus, proventriculus, pancreas, duodenum, small intestine, large intestine, cecum, cecal tonsils, bursa, and brain (Oldoni et al, 2009;Wang et al, 2013;Zhao et al, 2013).…”
Section: Occurrence Of Infectious Laryngotracheitis Virus (Iltv) In 2mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that DNA virus was detected in the larynx, trachea, lungs, cecum, kidney, pancreas, and esophagus of chickens experimentally infected with GaHV-1 (Wang et al, 2013). Another study (Oldoni et al 2009) showed that GaHV-1 has been more frequently detected in the conjunctiva, sinuses, and trachea, and the authors suggested that these tissues are the site of active replication. Nevertheless, detection of virus in the thymus and cecal tonsil was less frequent and not related to active replication.…”
Section: Pathological Immunohistochemical and Molecular Findings Inmentioning
confidence: 99%
“…In severe forms of the disease, haemorrhagic tracheitis together with gasping, coughing, and expectoration of bloody mucus are common. ILT occurs worldwide, and morbidity and mortality rates vary depending on the virulence of the circulating strain (Kirkpatrick et al, 2006a;Oldoni et al, 2009), the levels of virus circulating in the field and infections with other respiratory diseases of poultry (Guy & Garcia, 2008). With an overall mortality due to ILT that can reach 70%, large economic losses usually occur in highdensity poultry-producing regions (Bagust et al, 2000).…”
Section: Introductionmentioning
confidence: 99%